2014
DOI: 10.1093/ejcts/ezu026
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for neoaortic root pathology after the arterial switch operation

Abstract: After ASO, surgery for neoaortic root pathology may become necessary when follow-up is long enough and regardless of primary diagnosis or other risk factors. Redo neoaortic surgery can be performed with low risk taking into account the specific technical difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 22 publications
2
45
1
2
Order By: Relevance
“…While there are no reports suggesting increased risk of neo-aortic dissection or rupture at diameters <55 mm, data to establish specific surgical thresholds for post-ASO patients are lacking (table 3). Neo-aortic root operations are safe, despite technical challenges imposed by complex anatomy,97 but are uncommon up to 15 years after ASO 57 58…”
Section: Managementmentioning
confidence: 99%
“…While there are no reports suggesting increased risk of neo-aortic dissection or rupture at diameters <55 mm, data to establish specific surgical thresholds for post-ASO patients are lacking (table 3). Neo-aortic root operations are safe, despite technical challenges imposed by complex anatomy,97 but are uncommon up to 15 years after ASO 57 58…”
Section: Managementmentioning
confidence: 99%
“…The presence of aortic root dilatation has been demonstrated in up to 60% to 70% of patients after ASO; nonetheless, it does not tend to be progressive during late follow-up. Conversely, the progression of the degree of neoaortic valve insufficiency rarely occurs during the first 10 to 15 years after ASO, but it was found that it increases significantly later, and this is associated with the degree of postoperative neoaortic valve insufficiency at discharge soon after ASO [14,20,21]. Anatomic causes identified to be responsible for aortic root dilatation and neoaortic valve insufficiency included the presence of a ventricular septal defect and aortic/pulmonary mismatch and the postoperative geometry of the aortic root [19].…”
Section: Commentmentioning
confidence: 99%
“…The flow displacement direction from root to mid‐AAo also corresponded to the peak systolic WSS distribution in the mid‐AAo, but the contribution of FD on WSS distribution more upstream in the distal AAo was less compared with the effect of vessel tapering. The regions of abnormal increased WSS in the distal AAo clinically correlates with the location of the paper‐thin and fragile anterior wall of the AAo that has been found in ASO patients during root reoperations …”
Section: Discussionmentioning
confidence: 69%